Contemporary Usage of Riddles in Lithuania - Kensminienė, Aelita (Tautosakos darbai, 2022)
This empiric study surveys the existence of riddles and akin phenomena during the recent decade – both in written and oral, passive and active forms. The material includes schoolbooks and collections that publish riddles and have seen several editions in recent times; therefore, the survey embraces a longer period, reaching back to the restoration of Lithuanian independence. Material for the study also includes periodicals, internet sites and social media, as well as works by professional artists, advertisements and other media forms using classical riddles, their fragments, remakes and new compositions. Although recordings of the traditional folklore have almost ceased, the classical riddles retain their audience. They are frequently used in altered forms, but most of their functions are nevertheless preserved. The cases that are most similar to the traditional usage of riddles can be found in the virtual space – like Facebook. There is a tendency to adapt the old riddles to the modern realities; this is often tinted with political satire. The function of testing the participants’ knowledge and dexterity is readily visible in the context of “brain-battles” arranged by various bars and cafés, radio and TV programs, quizzes, contests, and internet. The traditional riddles, their fragments or newly created riddles that follow the typical riddle structure are willingly used as article captions, introductions, or image underlines. It is notable that people sometimes use riddles as indisputable facts or conveyors of the folk wisdom. This short survey could be regarded as a prelude to the comprehensive research into the contemporary riddles, which aims at finding out whether riddles and their performance exist nowadays as a phenomenon deserving scholarly attention.